Ion-momentum imaging of dissociative-electron-attachment dynamics in CO2, N2O, HCCH and CF4. (August 2015) - Fogle, M; Landers, A L; Moradmand, A; Sartor, J; Slaughter, D S; Haxton, D J; Rescignot, T N; McCurdy, C W; Weber, Th; Belkacem, A; Orel, A E; Matsika, S
Synopsis: We present experimental results for dissociative electron attachment to CO2, N2 O, HCCH and CF4 from an ion-momentum imaging technique. From our measured ion-momentum results we extract fragment kinetic energies and angular distributions. We directly observe the dissociation dynamics associated with the formation of transitory negative ions. We compare the experimental results with ab initio electronic structure and fixed-nuclei scattering calculations and obtain good agreement.